Humanising the Artificial: Anthropomorphism, Care, and Relational Self-Reconstruction in Deborah Install’s A Robot in the Garden - A, Divyadharshini; A, Manikandan; S, Surya; V, Saravanan; J, Charly Jerome (Asian Journal of Interdisciplinary Research, 2026)
This paper examines anthropomorphism as an ongoing literary process in Deborah Install's A Robot in the Garden, in which a human protagonist gradually develops a more responsible relational identity while an artificial being becomes socially intelligible. Based on multiple close readings of the 2015 Random House Canada edition, the study analyses sequences involving naming, pronoun use, bodily injury, comic resistance, separation, repair, and the transfer of caregiving practices. It distinguishes among three aspects that are often conflated in discussions of artificial companions: Ben's attribution of intention and emotion to Tang; the novel's use of first-person focalisation, dialogue, repetition, humour, and vulnerability to direct the reader's attention; and the ethical practices that follow from those attributions. The argument does not require proof of Tang's consciousness. Rather, Tang's material fragility and distinctive behaviour make him non-replaceable within Ben's emotional world, allowing curiosity to develop into care and care into sustained action. At the same time, the attachment has an unmistakable therapeutic dimension. Tang functions as a surface for projection, a substitute child, and, particularly at the beginning, a more manageable alternative to reciprocal human contact. The novel's principal transformation becomes visible when Ben applies the capacities acquired through robot-directed care to Amy and their unborn child. The article therefore argues that the ethical potential of anthropomorphism remains deliberately ambiguous. Ben's relationship with Tang gives him a stronger sense of accountability and relational agency, yet this development remains entangled with self-repair, consumer obsolescence, dependency, and paternalism. The study contributes to literary discussions of artificial intelligence and companionship by foregrounding narrative form and relational practice rather than making an unequivocal claim about machine personhood.